Serological Evidence Of Seasonal Variation Of Enteric Fevers - Damle A S; Tankhiwale N S; Kundinya D V; Thite G H (Wolters Kluwer Medknow Publications, 1985)
An attempt has been made to find out seasonal variation of enteric fever in this rural part of Maharastra. Diagnostic rise in antibodies against Salmonellae and clinical correlation was used to label the febrile cases as enteric fever cases over a period of six years. 4042 Samples were tested by Nidal reaction for rise in anti Salmonella antibodies. Of these 1236 (30%) showed significant (diagnostic) rise in antibody levels. Season wise study of these cases over the six years indicates that maximum number of enteric fever cases occur in rainy season followed by winter and summer. Chi-square test has been applied to find out statistical significance of these findings.